Keuangan Syariah: Solusi Inklusif untuk Pertumbuhan Ekonomi Perdesaan Kangean, Kabupaten Sumenep - Wafi Arman Faisal (Jurnal Inovasi dan Pengabdian, 2025)
The purpose of this study is to examine the approach in developing a sharia financial system with a focus on supporting sustainable economic growth in rural areas. Various aspects of the concept related to the principles of Islamic economics, rural needs, and the framework of sustainable development. The approach used will include literature reflection, data analysis, and in-depth conceptual discussion. From the results of this analysis, it is hoped that this article can provide better insight into how the development of a sharia financial system can be key to increasing sustainable economic growth in rural areas. The strategic role of financial products regarding sharia financial products that are in accordance with rural needs shows that the development of these products is very important to support sustainable economic growth. Products such as agricultural financing, livestock financing, and micro-business capital loans can provide a significant boost to rural economic development.